Analysis of the formation of radicals in biodiesel in contact with copper and metallic alloys via electronic paramagnetic resonance (EPR). (15th April 2019) - Chendynski, L.T.; Mantovani, A.C.G.; Savada, F.Y.; Messias, G.B.; Santana, V.T.; Salviato, A.; Di Mauro, E.; Borsato, D.
Highlights: Samples were analyzed with carbon silver and steel, copper and blackberry extract. The lowest values of oxidative stability were obtained for biodiesel with copper. The highest values of radicals formed were obtained for the sample with extract. Quantification of radicals formed was made via Electronic Paramagnetic Resonance. Abstract: This research evaluated the formation of free radicals in the oxidative degradation of biodiesel in contact with metallic copper and metal alloys via EPR using the spin trapping PBN, identifying and quantifying the formation of free radicals in commercial biodiesel samples. The biodiesel samples were analyzed in contact with carbon steel, silver steel, metallic copper and blackberry extract. The lowest values of oxidative stability were obtained for biodiesel in contact with metallic copper, followed by carbon steel and silver steel. The highest values of radicals formed were obtained for the sample containing blackberry extract. It was possible to identify radical species such as OH and CHOHCH3 during the decomposition of biodiesel.